Conventional water treatment plant in Karak, Bentong district, Pahang Darul Makmur / Nafhatun Jahirah Mohamed Azri - Mohamed Azri, Nafhatun Jahirah (Universiti Teknologi MARA UiTM,Perak, 2022)
The construction of the water treatment plant aims to treat water so that consumers can use it safely. Water treatment can remove contaminated or unsuitable components. A case study about the water treatment plant in Karak, Pahang. The main objective of this case study is to identify the process of water treatment. It is more focused on the process of how to go from raw water to treated water. It is also to explain the function of a backwash tank in a water treatment plant and to identify the type and installation of valves used.